2018
DOI: 10.3390/cryst8010020
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Framework Based on Polymeric Octamolybdate Anions and Copper(II) Complexes of Tetradentate N-donor Ligands

Abstract: (1a) with potentially accessible micropores as demonstrated by single-crystal X-ray diffraction measurements. Electron paramagnetic resonance spectroscopy analysis of 1 has also been assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
1
11
0
1
Order By: Relevance
“…200°C. This thermal behavior has been observed for other polyoxometalates ions with organic moieties (Iyer et al, 2014 ; Sánchez-Lombardo et al, 2014 ; Martin-Caballero et al, 2016 ; Dissem et al, 2018 ). Considering that the melting point of Metformin hydrochloride is 224°C (Benmessaoud et al, 2016 ), we can assign the endothermic peaks observed in the DTA thermogram in a temperature range of 190–210°C, to the melting of Metforminium cations (HMetf) present in Compound 2 .…”
Section: Resultssupporting
confidence: 65%
“…200°C. This thermal behavior has been observed for other polyoxometalates ions with organic moieties (Iyer et al, 2014 ; Sánchez-Lombardo et al, 2014 ; Martin-Caballero et al, 2016 ; Dissem et al, 2018 ). Considering that the melting point of Metformin hydrochloride is 224°C (Benmessaoud et al, 2016 ), we can assign the endothermic peaks observed in the DTA thermogram in a temperature range of 190–210°C, to the melting of Metforminium cations (HMetf) present in Compound 2 .…”
Section: Resultssupporting
confidence: 65%
“…In fact, we have always observed the trans-III form in all of our previous POM-Cu(cyclam) hybrid systems. [37][38][39][40] The crystal packing of compounds 1-Ln displays intrinsic layered nature and contains covalent 2-dimensional hybrid assemblies parallel to the (1-10) plane in which each dimeric POT is linked to four neighboring analogues along the [111] and [001] directions through the Cu1B and Cu1C moieties, respectively. Such connectivity follows a staggered brickwork grid pattern with rectangular intralamellar cavities of dimensions about 7.9 × 23.0 Å (Figure 3).…”
Section: Crystal Structure Of Compounds 1-lnmentioning
confidence: 99%
“…An additional example of a hybrid framework based on POM clusters and {Cu(cyclam)} 2+ metal-organic moieties showing robustness towards dehydration has been reported recently, namely [{Cu(cyclam)} 2 (Mo 8 O 26 )]Á1.5H 2 O (Dissem et al, 2018). The dehydration process into the [{Cu(cyclam)} 2 -(Mo 8 O 26 )] anhydrous phase does not proceed through an SCSC transformation in a strict sense, but through an SC-tocrystal transition, as the release of hydration water molecules from the parent compound has been found to result in nonmerohedral twinning and, hence, the single-crystal integrity is lost through the process.…”
Section: When Solvent Molecules Are Just Fillersmentioning
confidence: 99%